Analisis Efektivitas Iklan Layad Rawat Kota Bandung Berdasarkan Model AIDA (Studi Pada Pengunjung Event Bandung Air Show 9-12 November 2017) - Jatvika, Peggy Jatvika; Nurfebiaraning, Sylvie (Media Nusantara, 2021)
Ads are often chosen by the government to socialize and promote the programs they have because its considered as an effective form of information dissemination. With advertising, government-owned programs can be created and delivered in a variety of media ranging from conventional or print media, digital media, outdoor media, bellow the line media, and new media. As performed by the government of Bandung, which makes advertising to convey various information about Layad Rawat program massively to the citizens of Bandung. This study measures how effective advertising layad rawat bandung advertisement on mobile billboards (motorcycles and ambulances), which existed at the Bandung Air Show event on 9-12 November 201. Bandung Air Show event was chosen because it is considered effective to introduce Layad Rawat program to the public to see the number of visitors in 2016 and then reached about 80,000 people. This research uses a quantitative research method with a descriptive data analysis technique. Using total sampling technique with the number of respondents in the research as many as 100 people. The result of the percentage of each sub variable studied is 79% for sub variable of attention which can be interpreted that message of Layad Rawat advertisement about layad rawat is understood by the audience. 78.3% for sub variable interest that can be known that the respondent has an interest in Layad Rawat Bandung program after seeing the ads in the four media. 72.5% for sub variable desire which can be interpreted that layad rawat ads able provide stimulus audience to get involved further with layad rawat program. Last for 59.3% for the sub variable action which can be interpreted that the audience has not been able to make the audience to use layad care program of Bandung. The total percentage of Layad Rawat Bandung advertisement based on the AIDA model is 72.3%. Based on the calculation result in the rating category, the number is in the effective category.